Akurasi Sistem Penjadwalan Sholat Digital Menggunakan Arduino Sebagai Pengendali - Naf'an, Emil (Jurnal Sistim Informasi dan Teknologi, 2019)
This study aims to design and create a Digital Prayer Schedule system at Masjid UPI "YPTK" Padang using Arduino as a controller. Prayer schedule data can be taken from the Indonesian Ministry of Religion website and stored on a MicroSD card. Likewise with the lecturer activity schedule data, also stored in the MicroSD. This data is processed by the Arduino module based on the program stored therein. The output is in the form of a prayer times display on Seven Segments and a lecturer activity schedule display on Running Text. The first time the device is activated, it must be set up using the input button. The setting process includes setting the date, time and iqomah pause time settings. After the data is saved, it is automatically displaying the date, time and the prayer times on Seven Segments. The system also automatically displays the names of lecturers who are tasked with reading the Qur'an, sayings Asmaul Husna and praying on the Running Text based on data stored on the MicroSD card. Testing is done by activating the equipment for a week non-stop. The system is tested both in terms of component durability in operation and timeliness in activating the Buzzer when prayer time has entered. After testing the designed equipment, the date, time and prayer times can be displayed properly on Seven Segments and the schedule of lecturer activities also can be displayed well on the Running Text. Thus the system can be used and produced on a larger scale.